(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Dyslipidemia is a common metabolic complication among people living with HIV receiving antiretroviral therapy. As dolutegravir has become a cornerstone of first-line antiretroviral regimens, real-world data on lipid abnormalities among patients receiving dolutegravir-based therapy in low- and middle-income settings remain limited. Objective: To determine the prevalence of dyslipidemia, patterns of lipid abnormalities, and associated factors among HIV-infected patients receiving ART at the Hospital for Tropical Diseases. Methods: A cross-sectional study was conducted among 199 adult patients living with HIV who had been receiving antiretroviral therapy for at least one year at the Hospital for Tropical Diseases between August 2023 and July 2024. Dyslipidemia was defined as the presence of at least one abnormal lipid parameter (total cholesterol, triglycerides, LDL-C, or HDL-C). Logistic regression analyses were performed to identify factors associated with specific lipid abnormalities. Results: The overall prevalence of dyslipidemia was 84.9%, with low HDL-C being the most common dyslipidemia. In multivariable analyses, body mass index (aOR = 1,15) and duration of antiretroviral (aOR = 1,07) therapy were independently associated with hypertriglyceridemia, while low HDL-C was independently associated with lower baseline CD4 cell count (aOR = 3,70). Regimens containing lopinavir/ritonavir (aOR = 3,83) were associated with a higher risk of hypercholesterolemia, whereas dolutegravir-based regimens were associated with a significantly lower prevalence of total cholesterol abnormalities. Conclusions: Dyslipidemia is common among patients with HIV receiving antiretroviral therapy and predominantly manifests as an atherogenic–metabolic pattern characterized by low HDL cholesterol and elevated triglyceride levels rather than isolated hypercholesterolemia. These findings underscore the importance of comprehensive lipid assessment and the preferential use of metabolically favorable regimens in the long-term management of HIV infection.